Routine MR imaging of the internal carotid artery siphone: angiographic correlation with cervical carotid lesions. - Brant-Zawadzki, M (American Journal of Neuroradiology, 1990)
This study correlates the appearance of the cavernous segment of the carotid artery on MR images with the presence of significant stenosis or occlusion of the cervical carotid artery as seen on angiograms in 100 patients who had brain MR imaging and arteriography within a 1-week period. Four patients demonstrated isointense signal within the carotid artery's cavernous segment; two of these findings correlated with complete carotid occlusion as seen angiographically, while partial compromise was seen angiographically in the other two. Four other patients had variable signal intensity and irregularity of the luminal outline in the carotid siphone, correlating with angiographic evidence of atheromatous disease in three patients and of dissection in one patient. The demonstration of normal signal void within a normal-appearing cavernous segment of the internal carotid artery in the remaining 92 patients correlated with absence of significant stenosis within the cervical segment in 86 patients. In the remaining six, significant disease of the internal carotid artery was found. Isointensity within the intracranial carotid artery can indicate either complete occlusion or very slow flow. Therefore, angiography is still necessary to completely exclude potentially treatable disease that produces very slow flow leading to isointensity. The presence of normal flow void in the intracranial segment does not exclude significant compromise of the cervical segment of the carotid artery.